The Vegetation of Mothronwala Swamp Forest (Plant Communities of Swampy Zone) - Dakshini, K. M. M. (Indian Forester, 1960)
Based on quadrat studies, fourteen plant communities have been recognised in the swampy zone of the Mothronwala swamp forest near Dehra Dun. Some of the communities recognised form pure and open stands while others are of mixed and closed type.